The first list of amphibians and reptiles from Soc Son watershed protection forest, Ha Noi City, Vietnam - Tung, Tran Thanh; Dung, Le Trung (Academia Journal of Biology, 2021)
Based on a new herpetological collection from four field surveys conducted in the Soc Son Watershed Protection Forest, Ha Noi City, from March 2017 to April 2018. We herein provide the first list of 42 species of amphibians and reptiles, in which, 12 species are newly recorded for the herpetofauna of Ha Noi City. In addition, morphological characters of these species are also provided. In terms of conservation concern, two species are listed in the IUCN Red List (2020), five species are listed in the Vietnam Red Data Book (2007), and two species are listed in the Governmental Decree No 06/2019/ND-CP.